ANALISIS PEMAHAMAN LITERASI DATA MAHASISWA PGSD DALAM MEREFRESENTASIKAN DATA SOFTWARE EXCEL DAN SPSS PADA MATA KULIAH STATISTIK - Silalahi, Taruli Marito; Limbong, Winny Sunfriska (Fakultas Ilmu Pendidikan Universitas Sari Mutiara Indonesia, 2021)
This study aims to analyze the understanding of PGSD students on data literacy skills using Microsoft Excel and SPSS. This type of research uses a qualitative approach with the type of case study method that aims to describe students' understanding of data literacy using Excel and SPSS software. The sample in this study was 25 students of 6th semester who were randomly selected from the total 6th semester students in the PGSD program study. The instruments used were interview, observation sheets, mid and final tests. Data analysis in this study is data reduction as a selection process, focusing on simplification, abstraction and transformation. The results showed that students' understanding of data literacy using Microsoft Excel with an average of 84.20 in the medium category and SPSS with an average of 87.47 being in the high category.